Warriors of the Plains - Bonnie Lynn-Sherow (Symphony in the Flint Hills, 2013)
Portraits of famous Native American and US Army warriors by artists Corbis, George Catlin, Thomas Read, and George Peter Alexander Healy
Keywords: George Armstrong Custer; Great Plains; Plains; warrior; army; military; Sitting Bull; Native Americans; Indian; chief; tribe; tribal; Philip Sheridan; La-do& #x27; O-ke-a; Buffalo Bull; Pawnee Warrior; Pawnee; William Techumseh Sherman; Shon-ta-yi-g; Little Wolf